2019
DOI: 10.1039/c8ra09026b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine NiMoOx nanoparticles confined in mesoporous carbon for the reduction of nitroarenes: effect of the composition and accessibility of the active sites

Abstract: Ultrafine NiMoOx NPs were confined in the framework of mesoporous carbon by using the replication method for the reduction of nitroarenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…43 Li et al 44 prepared MoS 2 @-TiO 2 @poly(methyl methacrylate) by freeze drying hydrothermally treated electrospun PMMA nanobers containing titanium n-butoxide and MoS 2 nanosheets and degraded MO (10 mg L À1 , 100 mL) completely in 40 min under UV light irradiation. Li et al 45 reported a general approach for the synthesis of ultrane NiMoO x NPs conned in mesoporous carbon with different morphologies and compositions using the replication method with SBA-15 as a hard template and studied their reduction efficiency towards 4-NP. Our research group synthesized Cu-based oxysulde catalysts (CuBiOS, CuVOS, CuSbOS, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…43 Li et al 44 prepared MoS 2 @-TiO 2 @poly(methyl methacrylate) by freeze drying hydrothermally treated electrospun PMMA nanobers containing titanium n-butoxide and MoS 2 nanosheets and degraded MO (10 mg L À1 , 100 mL) completely in 40 min under UV light irradiation. Li et al 45 reported a general approach for the synthesis of ultrane NiMoO x NPs conned in mesoporous carbon with different morphologies and compositions using the replication method with SBA-15 as a hard template and studied their reduction efficiency towards 4-NP. Our research group synthesized Cu-based oxysulde catalysts (CuBiOS, CuVOS, CuSbOS, etc.)…”
Section: Introductionmentioning
confidence: 99%